Puzzle of Indian democracy: a reinterpretation - Lijphart,Arend (New Delhi, 1994)
Almost all the countries which gained independence from colonial rule in this century, adopted initially the democratic form of government. In many, it lasted only for brief periods and the countries slided into dictatorship of one kind or another. Some of the countries have since been passing through periods of dictatorship and attempts at some form of democratic government. India is one of the few newly independent countries in which democracy has endured since 1947. This has puzzled many in the world. How could a poor country with a large population and with immense diversity in levels of development, language, religion and sects and, to some extent, in ethnicity be united and democratic? The world had not seen a democracy like this before. It looked and sounded chaotic; not all the students of Indian political system were convinced of its viability and sustainability. Many predicted its fall sooner rather than later. But defying all the established theories and prognosis, Indian democracy survived. That is not to argue that it was a perfect achievement or that it satisfied all the sections of the Indian society. But it was viable enough to weather all the difficulties which the country experienced in the decades of her independent existence as a nation-state.
Keywords: Democracy-India